THE USE OF ANIMATION MOVIE TOWARDS STUDENTS SPEAKING ABILITY THROUGH E-LEARNING - Sri Wahyuni; Maulizan Maulizan; Yulidarawati Yulidarawati (Jurnal Ilmiah Teunuleh, 2021)
This study is the use of English animation movie as a media in teaching speaking through e-learning process, and it is intended to improve the speaking ability of the students. The methodology used is classroom action research and SMA Keberbakatan Olahraga Negeri (SMAKON) Aceh as a research subject. The source of the data in this study is from the communication between teacher and students in teaching and learning process through e-learning. The instruments are used observation and test. The data observation is analyzed by using qualitative method and the data from the test is analyzed by using quantitative method. In the pre-test result, there are only 1 student who complete pre-test from the total 4 students who followed pre-test. The percentage is still under the predictive criteria, specifically ? 80% from the average score of students that is ? 65. Meanwhile, the post-test shown that all four students got exhaustive score with the percentage reached 50% and the score average reached 50. It means that X IPS-1 student’s improving speaking by using animation movie on e-Learning process at SMAKON is in good category. On the observation result of X IPS-1 students’ improving speaking on e-Learning process improves. Before the researcher implemented animation movie, the percentage only reached 25%, either student’s improving on e-Learning process or students’ activity during teaching and learning process. Then, the percentage increased to 100% for students’ improving speaking on e-Learning process and 83.75% for students’ activity during teaching and learning process after animation movie has implemented.